Catalytic Dealkylation of Ethers to Alcohols on Metal Surfaces. Issue 34 (19th July 2016) - Yang, Biao; Lin, Haiping; Miao, Kangjian; Zhu, Pan; Liang, Liangbo; Sun, Kewei; Zhang, Haiming; Fan, Jian; Meunier, Vincent; Li, Youyong; Li, Qing; Chi, Lifeng
Abstract: On‐surface synthesis has prompted much interest in recent years because it provides an alternative strategy for controlling chemical reactions and allows for the direct observation of reaction pathways. Herein, we combined scanning tunneling microscopy and density functional theory to provide extensive evidence for the conversion of alkoxybenzene‐containing ethers into alcohols by means of surface synthesis. The reported dealkylation reactions are finely controlled by the annealing parameters, which govern the onset of successive alkyl chains dissociations. Moreover, density functional theory calculations elucidate the details of the reaction pathways, showing that dealkylation reactions are surface‐assisted and very different from their homogeneous analogues in solution. Abstract : On‐surface dealkylation : The dealkylation reaction from ethers to alcohols is controllably realized through on‐surface synthesis techniques. This reaction was shown to be surface‐assisted and universal for alkoxybenzene‐containing ethers.